A Christian anarchist?: Gregory of Nyssa's criticism of political power - Steenbuch, Johannes Aakjær (Political theology, 2016)
The Cappadocian Church father Gregory of Nyssa (c. 335-395 AD) frequently attacks political power and domination in different forms. He does not present a systematic political philosophy, but there is a range of underlying theological, anthropological and moral philosophical ideas at play in Gregory's criticism. Especially important is Gregory's theological anthropology, and the unity of humankind. In this article it is argued that Gregory's political thinking can be described as "anarchism", in so far this is defined as the universal rejection of all kinds of domination and the identification of justice with any positive political state of affairs.